HUBUNGAN AKTIVITAS FISIK TERHADAP KEJADIAN OSTEOPOROSIS PADA LANSIA DI DESA TANJUNG KURUNG ILIR KABUPATEN LAHAT - Aulianah, Hili; Agustina, Nuriza (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2021)
Increasing life expectancy today has consequences with the emergence of various health problems in the elderly. One of the diseases commonly experienced by the elderly is Osteoporosis. In the village Tanjung Kurung Ilir, the elderly suffer from bone deformities. This study aims to determine the relationship of physical activity to the incidence of osteoporosis in the elderly 2020. The population in this study was all elderly, totaling 39 people. The sample of this study is the whole total population. This study uses a